(untitled) (Research, Society and Development, 2020)
The present study aims to understand the perceptions of caregivers of the elderly about the meanings, feelings and motivations of the act of caring. It is a descriptive, exploratory field research with a qualitative approach, developed in the municipality of Floriano/PI, in the home setting of 20 caregivers for the elderly. The interpretation of the caregivers’ speeches made it possible to identify that the participants perceive the act of caring in three categories: support for the basic human needs of the elderly, mutual relations and situations inherent to the caregiver. Most caregivers related the care provided to meeting the psychobiological and psychosocial needs. Mutual relationships are visualized in the feelings of gratitude, pleasure, satisfaction and love expressed, in addition to marital ties. The main situations inherent to care were the difficulty in care, the fear of losing the loved one, the obligation, retribution, and the fact that some did not have someone else to take care of or help with the execution of tasks. Thus, the interpretation of the speeches made it possible to identify their conceptions about aspects of care and the dubious feelings that permeate this activity. The analyzes raised the need for support by health teams in this context, providing support and guiding the caregiver both in the act of caring for others and for oneself.